THE THE EFFECT OF HEPATOPROCTECTIVE PROPOLIS ON THE HISTOPATHOLOGY OF THE LIVER CELL MICE INDUCED BY PARACETAMOL - Salsabila, Shofa; Yazid, Noor; Marfu’ati, Nanik (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
The overdose of paracetamol utility may increase N-acetyl-p-benzoqui-noneimine (NAPQI) and produce the free radicals, which will cause liver cell damage. Propolis contains antioxidants which have the ability to capture free radicals The aim of this study is to identify the hepatoprotective effect of propolis doses of 0.4 ml and 0.8 ml on the histopathological appearance of the liver of mice induced by paracetamol. This research was an experimental research using the Post Test Only Control Group Design method. The sample of this study were 24 Swiss Webster mice divided into 4 groups: group (K-) not given propolis and paracetamol; group (K+) was given paracetamol at a dose of 338 mg/kgBB; group (P1) was given a dose of 0.4 ml of propolis and group (P2) 0.8 ml and then induced by paracetamol at a dose of 338 mg/kgBB. This research was conducted for 14 days and on the 15th day termination was carried out to observe the histopathological picture of the liver tissue. There was a statistically significant hepatoprotective effect of propolis in the histopathological picture of the liver in the K- group under normal circumstances (score 1), the K+ group was dominated by necrosis (score 4), the P1 group was dominated by normal cells (score 1) and the P2 group was dominated by hydropic degeneration (score 3). The Kruskal-Wallis test showed a significant difference in all treatment groups with p<0.001. The results of the Mann-Whitney test showed that between the K– group and the K+ group and the P2 group there was a significant difference, between the K+ group and the P1 and P2 groups there was a significant difference, and between the P1 group and the P2 group there was a significant difference with p<0,05. There was a hepatoprotective effect of propolis on the histopathological of the liver of mice induced paracetamol. Propolis dose of 0.4ml was more optimal in preventing damage to the liver of mice than a dose of 0.8ml.